Analysis of Chinese Tourists Occur Safety Problem in Chiang Mai Thailand - Feifei Jiang (2020)
© 2020 IEEE. The main purpose of this article was to design a Tourist Safety Knowledge Map for Chinese tourist travel to Chiang Mai, Thailand. The data of this paper were from related Chinese tourism website and Thai government officially department, it would use to identify the research problem of this paper. Then the Focus Group and Common KADS-knowledge model would be representative of Demand side and Supply side in the step of research methodology. The research result of this paper would include the precaution of Chinese tourist visit Chiang Mai and also the solution after Chinese tourist occur safety problem in Chiang Mai. Chinese tourist could check matters that need be attention in the Knowledge Map.